Fatwa and violence in Indonesia - Assyaukanie, Luthfi (The journal of religion & society, 2009)
Fatwa is often considered as a non-binding legal opinion. Some jurists use this caveat to reject any links between fatwa and violence. They argue that fatwa is one thing and violence is something else. This article is an attempt to disprove such a misleading argument by providing cases that took place in Indonesia. I argue that there is a strong connection between fatwa and intolerant actions.